2010
DOI: 10.1088/0268-1242/25/8/085006
|View full text |Cite
|
Sign up to set email alerts
|

Quasiclassical description of the nearest-neighbor hopping dc conduction via hydrogen-like donors in intermediately compensated GaAs crystals

Abstract: Expressions for the pre-exponential factor σ 3 and the thermal activation energy ε 3 of hopping electric conductivity of electrons via hydrogen-like donors in n-type gallium arsenide are obtained in the quasiclassical approximation. Crystals with the donor concentration N and the acceptor concentration KN at the intermediate compensation ratio K (approximately from 0.25 to 0.75) are considered. We assume that the donors in the charge states (0) and (+1) and the acceptors in the charge state (−1) form a joint n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“… Средняя по объему кристаллического образца концентрация доноров в зарядовом состоянии (+1), согласно [28], определяется так: , , / a H -боровский радиус.…”
Section: ионизационное равновесие в кристаллических полупроводникахunclassified
“… Средняя по объему кристаллического образца концентрация доноров в зарядовом состоянии (+1), согласно [28], определяется так: , , / a H -боровский радиус.…”
Section: ионизационное равновесие в кристаллических полупроводникахunclassified
“…In this work in the weak electric field limit (e d k T B E  , where d is the mean hop length of electron via localized states) and when the thermal energy is greater than the fluctuation dispersion of energy levels of localized states it is shown that the ratio of the diffusion coefficient to the drift mobility is equal to k T e B . Finally, the values of effective hole or electron concentrations involved in hopping migration via hydrogenlike impurities in crystalline semiconductors are determined in [13,16,17,[28][29][30]. [31][32][33][34] used particular forms of the expressions for N hp and N hn that are only suitable for limiting values of the compensation ratio (K 1  or K 1 1 - ) of the majority impurity by the minority impurity.…”
Section: At Temperatures T T Jmentioning
confidence: 99%
“…According to [46,57] only the linear approximation of the screening charge density  . Taking into account equations (3) and (7), the radius of static screening of the Coulomb field of the impurity ion by v-band holes and holes of the acceptor band migrating over the crystal is determined by the following expression (see also [26,28,29,46]): = ---( ) according to equations (1) and (6) is the effective concentration of holes hopping via acceptors in the vicinity of the screening ion; p…”
Section: Statistics Of Holes In Valence and Acceptor Bandsmentioning
confidence: 99%
See 2 more Smart Citations